Influence of low concentration of diamond water nanofluid in loop heat pipe - Aun T.S.; Abdullah M.Z.; Gunnasegaran P. (International Information and Engineering Technology Association, 2023)
Costs; Diamonds; Fluids; Heat pipes; Heat resistance; Heat transfer; Heat transfer coefficients; Specific heat; Thermal conductivity; Heat transfer characteristics; Heat transfer performance; Loop Heat Pipe; Low concentrations; Mass concentration; Nanofluids; Thermal Performance; Transient temperature distributions; Nanofluidics